Factor VIII Inhibitor and Bronchogenic Carcinoma - Al-Ismail, S A D; Parry, D H; Moisey, C U; Bloom, A L (Thrombosis and Haemostasis, 1979)
An inhibitor to procoagulant factor VIII (FVIIIC) developed in a patient three years after palliative resection of a bronchogenic carcinoma. The inhibitor was not active against ristocetin cofactor but possibly had some activity against factor XI. It responded to immunosuppressive therapy. This is apparently the first reported association of carcinoma and factor VIII inhibitor.